A critical introduction to fictionalism - Kroon, Fred; Brock, Stuart 1968-; McKeown-Green, Arthur Jonathan 1963-2015 (Bloomsbury critical introductions to contemporary metaphysics, 2019)
"A Critical Introduction to Fictionalism provides a clear and comprehensive understanding of an important alternative to realism. Drawing on questions from ethics, the philosophy of religion, art, mathematics, logic and science, this is a complete exploration of how fictionalism contrasts with other non-realist doctrines and motivates influential fictionalist treatments across a range of philosophical issues. Defending and criticizing influential as well as emerging fictionalist approaches, this accessible overview discusses physical objects, universals, God, moral properties, numbers and other fictional entities. Where possible it draws general lessons about the conditions under which a fictionalist treatment of a class of items is plausible. Distinguishing fictionalism from other views about the existence of items, it explains the central features of this key metaphysical topic. Featuring an historical survey, definitions of key terms, characterisations of important subdivisions, objections and problems for fictionalism, and contemporary fictionalist treatments of several issues, A Critical Introduction to Fictionalism is a valuable resource for students of metaphysics as well as students of philosophical methodology. It is the only book of its kind"--Provided by publisher.